Reducción sostenido del trabajo infantil como resultado de la política pública del estado hacia el buen vivir y su impacto social en el cantón El Empalme provincia del guayas periodo 2012-2013 - Monserrate García, Estefany Moncerrate (2015)
This research work was conducted in El Canton THE splice located 167 km from Guayaquil and 21 km from Quevedo in the Guayas Province during 2013-2014 and had overall objective evaluate public policy undertaken in 2012-2013 to the elimination or reduction of child labor and its social impact in Canton El Empalme Guayas province. After obtaining the objectives, assumptions and variables of research preceded the development of the theoretical framework where a variety of deployed themes theme and aims and objectives were met in information gathering survey methodology was also used and interviews to define objectively the most important points of research. In the results we can see that these were analyzed and especially possible to verify the hypothesis of the research, which was: The eradication of child labor has had a strong impact on the overall development of children and adolescents in their families in Canton the Empalme Guayas Province, 2012-2013.The conclusions and recommendations summarize the research conducted, as well as allowed to know the socio-economic needs and impacts of child labor in the village of El Empalme